Some sesquiterpenoids and 5α,8α-epidioxysterols from Solanum lyratum - Yu, S.M.; Kim, H.J.; Woo, E.-R.; Park, H. (1994)
From the stems of Solanum lyratum Thunb. (Solanaceae), two sesquiterpenoids together with two 5α,8α-epidioxy sterols have been isolated and identified as atractylenolide I, dehydrocarissone, ergosterol peroxide, 9,11-dehydroergosterol peroxide. These compounds never prviously isolated from this genus. ？ 1994, The Pharmaceutical Society of Korea. All rights reserved.